ADAPTASI PRAKTISI MEDIA TERHADAP MIGRASI SISTEM PENYIARAN NASIONAL DARI ANALOG KE DIGITAL (STUDI FENOMENOLOGI PADA INDUSTRI PENYIARAN) - Asri, Rahman (Jurnal Ranah Komunikasi, 2024)
This study aims to describe the adaptation process of broadcasters about the migration from analog to digital broadcasting system in the Analog Switch Off (ASO) process being carried out since November 2, 2022 in the national broadcasting system. According to the Omnibus Law specially in article 60A (paragraph2) that migration of terrestrial broadcasting (free to air) from analog system to digital technology and termination of the analog broadcast process must be completed no later than two years. This qualitative research will conduct in-depth interviews to find out an experience and understanding, what is felt broadcasters and think about in the adaptation process. The research results, in general, the process of digitizing broadcasting is a necessity. The socialization and demanding for Set Top Box (STB) that the community needs, as well as the readiness of infrastructure is the challenges for next steps, changes media landscape, competition mapping, viewing preferences to preferred contents. For broadcast must be more efficient and conditioned the role of multi-tasking and more efforts to attract the attention of audiences. The recommendations suggested, the socialization of migration of the national broadcasting system (ASO) must continues, the provision of Set Top Box (STB) tools must be more equitable and affordable for all levels of society.